TECHNICAL EFFICIENCY OF DAIRY CATTLE FARMS IN THE EASTERN MEDITERRANEAN REGION OF TURKEY BY STOCHASTIC FRONTIER ANALYSIS - O. Parlakay; H. Yilmaz; M. Gül; S. Akkoyun; M. E. Bilgili; Y. Vurarak; H. Hizli; N. Kiliçalp (Journal of Animal and Plant Sciences, 2017)
The aim of this study was to determine the technical efficiency of dairy cattle farms in Turkey. The main material of the study consists of primary data that were gathered in 2012 from 148 dairy cattle farms in the Eastern Mediterranean Region by the face to face interview method. Data were analyzed using the Stochastic Frontier Analysis method. The effects of socio-economic variables on technical efficiency were calculated using the SFA TE Effects Model. According to research results, the average technical efficiency score was found as 79%. Positive correlation between milk production and the amount of roughage usage, and negative correlation between milk production and labor force usage were found. The socio-economic variables of education, dairy cattle experience and labor force indexes were found positive. However, only dairy cattle experience was found to be significant among these variables. According to the research results, sourcing was found to be sufficient in dairy cattle farms; whereas, efficiency was found insufficient. It is possible to get higher productivity with the same amount of input usage by managing the production process as well.
Keywords: Dairy cattle; Technical efficiency; Stochastic Frontier Analysis; TE Effects Model